Firearm availability and parricide - Mills, Samantha J. (Journal of family violence, 2023)
The association between firearm ownership and homicide has been shown to be specifically related to homicides involving intimate partners and other domestic relations. Prior research has shown that firearms are commonly used in parricide, and in particular parricides perpetrated by youth. This study examined whether higher levels of firearm ownership are associated with increased rates of parricide, and whether this association was stronger among youthful offenders. We used a longitudinal design and negative binomial regression to model parricide as a function of household firearm ownership at the state level using data from the Federal Bureau of Investigation’s Supplementary Homicide Reports from 1981 through 2018. There were 8,916 parricide perpetrators in the study sample, and nearly half used a firearm (47.7%). Whereas parricides committed by adults involved firearms in 43.5% of cases, almost two-thirds (64.8%) of parricides committed by youth involved firearms. Each 1-percentage point increase in state-level household firearm ownership was associated with a 1.5% increased incidence of parricide (95% CI = [0.6%, 2.4%], p = .001). Moderation analyses revealed that the association between state-level firearm ownership and parricide was between 2.6- and 3.6-fold stronger for incidents perpetrated by youth relative to adults. Reducing youth access to firearms in the context of conflictual parent–child relations represents one strategy for reducing parricide.